2017
DOI: 10.1007/s10067-017-3823-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of eculizumab in a systemic lupus erythemathosus patient presenting thrombotic microangiopathy and heterozygous deletion in CFHR1-CFHR3. A case report and systematic review

Abstract: The association of thrombotic microangiopathy (TMA) with systemic lupus erythematosus (SLE) has been described in 0.5 to 10% of cases, and patients present worse outcome. TMA is described as the association of microangiopathic hemolytic anemia, thrombocytopenia, and an organ injury, frequently the kidney. This study describes a successful case of use of eculizumab in a patient with SLE and TMA refractory to standard therapy, and provides a literature review. Case description and search in PubMed and MEDLINE us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…A recent study reviewed 20 patients who received eculizumab with SLE and/or APS until 2017, where a hematological response was evident in 100% of the patients, and kidney recovery was evident in 85% of the patients. This study suggested that eculizumab might be a potential alternative treatment for patients with SLE and/or APS presenting with TMA and who were refractory to current immunosuppression therapies [57].…”
Section: Therapeutic Strategies For Renal Microvascular Lesions In Lnmentioning
confidence: 79%
“…A recent study reviewed 20 patients who received eculizumab with SLE and/or APS until 2017, where a hematological response was evident in 100% of the patients, and kidney recovery was evident in 85% of the patients. This study suggested that eculizumab might be a potential alternative treatment for patients with SLE and/or APS presenting with TMA and who were refractory to current immunosuppression therapies [57].…”
Section: Therapeutic Strategies For Renal Microvascular Lesions In Lnmentioning
confidence: 79%
“…Six further articles were excluded at this stage (involving 7 patients): two involved the same patient cases duplicated between published journals and published conference abstracts, one study reported a patient with SLE who was excluded before the end of the study, one study looked at four patients, two of whom had lupus but the results were not stratified by diagnosis and so were uninterpretable, one study reported a patient with SLE who was given eculizumab to treat an episode of aHUS caused by Dengue fever [25], and one study reported a patient with inactive SLE who was given eculizumab to treat Degos disease [26]. Therefore, 14 papers were included in the systematic literature review [21,[27][28][29][30][31][32][33][34][35][36][37][38][39] (Fig. 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…136,137 Anticomplement therapies may be considered in catastrophic APS, thrombocytopenic purpura, complement-mediated TMA, and recurrent TMA in an allograft. [138][139][140][141] Anticoagulation remains the standard of care when APS is present. 142 However, the impact of anticoagulation on renal lesions is unclear, and many patients experience a decline in kidney function despite therapeutic anticoagulation.…”
Section: Special Circumstancesmentioning
confidence: 99%